Global Plantations in the Modern World
XXV, 370 p. 33 illus., 30 illus. in color.
Keywords: Taking a multidisciplinary and global approach, this edited book examines the dynamic role of plantations as productive, socio-political and ecological forms throughout imperial and post-colonial worlds spanning multiple and broad temporalities. Showcasing an expansive range of case studies across different geographies, the collection sheds light on the heterogeneity of plantations and offers insights into the afterlives, spectres and remnants of systems that have been analysed as schemes of production, extraction and authority. Focusing on the expansion of plantation systems throughout various political-economic and ecological projects, and across the modern (and post-modern) period, allows the authors to move beyond analyses that often deal with individual empires through human-centered lenses. The contributors explore resistance to the mechanisms of extraction and control that plantations and their afterlives demanded, shedding light on their excesses, contradictions, failuresand deviations. Offering a comprehensive treatment of global plantations, this book provides valuable reading for researchers with an interest in the socio-political and environmental effects of colonialism and imperialism in their various guises. Chapters 1, 8 and 11 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com. Irene Peano is an Assistant Researcher in the Institute of Social Sciences at the University of Lisbon, Portugal. She researches the processes of migrant farm-labour and agribusiness organisation in contemporary Italy and their genealogies. Marta Macedo is a Postdoctoral Researcher in the Institute of Social Sciences at the University of Lisbon, Portugal. Her work focuses on São Tomé plantations, mixing approaches from the history of science and technology, environmental history and labour studies. Colette Le Petitcorps holds a PhD in Sociology at the University of Poitiers (France). She is currently a postdoctoral researcher associated with the Centre d’études en sciences sociales sur les mondes africains, américains et asiatiques (Center for social studies on African, American and Asian worlds) in Paris. She works on gender, labour relations and the economy of the poor in the post-plantation, with the case of contemporary Mauritius.